REGULATION OF THE PROFESSIONAL ACTIVITY OF LEGAL CONSULTANTS - Kiyazova , Альбина Жомартовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
Legal consultants are the important component of the system of ensuring legal and social protection of the population, as well as maintaining law and order and justice in society. The importance of the professional activity of these persons determines the need to establish requirements for their qualifications and for the organization of the activity itself. This article examines the historical experience and features of state and alternative regulation of the activities of legal consultants. The initial regulation of the activities of persons providing paid legal services, from 1997 to 2005, was carried out at the state level through licensing and state control, then the activities of these persons were regulated in a civil law manner. In 2018, a specialized legislative act defined the status of a legal consultant and chambers of legal consultants, as well as fixed the mechanism for self-regulation in the field of legal assistance with mandatory participation of consultants in a self-regulatory organization. The article examines the provisions of legislative acts regulating the procedure for regulating the activities of legal consultants. Currently, the state imperatively establishes regulatory requirements for the qualifications of legal consultants, and also indirectly influences their activities by exercising regulatory, implementation and control functions in relation to the chambers in which they are members. In the context of self-regulation, it is the chambers that directly affect the activities of legal consultants, since they are endowed with regulatory and supervisory powers in relation to their members. The results of this study are to identify the specifics of regulating the activities of legal consultants, through different periods, as well as to identify the individual shortcomings of the current regulatory mechanism both in legislative acts and in practice of their application, with the development of proposals to eliminate them.